Chemical heterogeneity in interfacial layers of polymer nanocomposites. Issue 23 (29th May 2018) - Yang, Siyang; Liu, Siqi; Narayanan, Suresh; Zhang, Chongfeng; Akcora, Pinar
Abstract : A lower molecular weight of the matrix enhances the reinforcement of PMMA adsorbed nanoparticles in PMA composites above the T g of both polymers. Abstract : It is well-known that particle–polymer interactions strongly control the adsorption and conformations of adsorbed chains. Interfacial layers around nanoparticles consisting of adsorbed and free matrix chains have been extensively studied to reveal their rheological contribution to the behavior of nanocomposites. This work focuses on how chemical heterogeneity of the interfacial layers around the particles governs the microscopic mechanical properties of polymer nanocomposites. Low glass-transition temperature composites consisting of poly(vinyl acetate) coated silica nanoparticles in poly(ethylene oxide) and poly(methyl acrylate) matrices, and of poly(methyl methacrylate) silica nanoparticles in a poly(methyl acrylate) matrix are examined using rheology and X-ray photon correlation spectroscopy. We demonstrate that miscibility between the adsorbed and matrix chains in the interfacial layers led to the observed unusual reinforcement. We suggest that packing of chains in the interfacial regions may also contribute to the reinforcement in the polymer nanocomposites. These features may be used in designing mechanically adaptive composites operating at varying temperature.